Asymptomatic and Subclinical Mpox: An Association With Modified Vaccinia Ankara Vaccine - Golden, Matthew R; Soge, Olusegun O; Mills, Margaret; Berzkalns, Anna; Cannon, Chase; Ramchandani, Meena; Dombrowski, Julia C; Karmarkar, Ellora N; Chow, Eric J; Gov, Jolene P; Swenson, Paul; Greninger, Alexander L (Sexually transmitted diseases, 2024)
How often mpox causes asymptomatic infections, particularly among persons who have received the Modified Vaccinia Ankara (MVA) vaccine, is unknown. We performed mpox polymerase chain reaction testing on rectal and pharyngeal specimens collected from symptomatic and asymptomatic patients at a sexual health clinic in Seattle, WA, between May 2022 and May 2023. Analyses evaluated the prevalence of asymptomatic or subclinical infection and, among persons with polymerase chain reaction-positive tests, the association of MVA vaccination status with the symptomatic infection. The study population included 1663 persons tested for mpox during 2353 clinic visits. Ninety-three percent of study participants were cisgender men and 96% were men who have sex with men. A total of 198 symptomatic patients (30%) had a first mpox-positive test during 664 visits. Eighteen patients (1.1%) tested during 1689 visits had asymptomatic or subclinical mpox based on a positive rectal or pharyngeal test done in the absence of testing done because of clinical suspicion for mpox. Fourteen (78%) of 18 persons with asymptomatic/subclinical mpox and 53 (26%) of 198 persons with symptomatic mpox had received at least 1 dose of the MVA vaccine ( P < 0.0001). Controlling for calendar month, study subjects who received 1 and 2 doses of MVA vaccine were 4.4 (95% confidence interval, 1.3-15) and 11.9 (3.6-40) times more likely to have asymptomatic versus symptomatic mpox, respectively, than persons who were unvaccinated. Asymptomatic mpox is uncommon. Modified Vaccinia Ankara vaccination is associated with an asymptomatic/subclinical infection among persons with mpox.